Redesain Panti Asuhan Anak Naungan Kasih St. Elisabeth Dengan Pendekatan Arsitektur Neo – Vernacular Ende Lio Di Kota Ende - Mbuu, Alfons (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2022)
St. Shade of Love Children's Orphanage Elisabeth is a potential solution to be developed and redesigned to complement the limited facilities to support children's activities at this orphanage for the next few years considering that there are still many orphans and neglected children who cannot be accommodated. and fostered, because as a container or home, the St Elisabeth Children's Orphanage has a special task of providing care for children aged infants/infants (0-1.5 years), children aged toddlers/toddlers (1.5 -3 years), pre-school age children (3-5 years), school age children (5-10 years), junior high school children, high school / vocational school children, children college students and working-age children whose lives are neglected. With the concept of the Neo-Vernacular Ende-Lio architectural design approach, the Orphanage presents new facilities to support existing activities at this Orphanage, the existing Main Facilities and Supporting Facilities are arranged in such a way as to apply the Neo-vernacular Architectural Concept in the interior and exterior of the building. The pattern of building layout and circulation in the inside and outside of the building is closer to the Ende-Lio vernacular concept. This redesign is expected to answer the needs of Ende Lio architectural cultural expression in a real way in modern developments